Association Between Hyperhomocysteinaemia and Cardiovascular Diseases In Type-II Diabetes (Medical Forum Monthly, 2024)
Objective: To study the relationship between cardiovascular diseases and increased level of homocysteine in Type II diabetes. Our study was aimed to find out the Hyperhomocystenemia as a marker for early prediction of Cardiovascular (CVD) diseases in patients suffering from Type II diabetes mellitus.Study Design: Prospective study.Place and Duration of Study: This study was conducted at Baqai Institute of Diabetology & Endocrinology (BIDE) and Agha Khan University (AKU), Karachi, Pakistan from July 2016 to Oct. 2016.Materials and Methods: The study included a total of eighty (80) Type II diabetes (40 Males and 40 Females) and forty (40) healthy subjects were selected as Control. All biophysical parameters and biochemical tests were done using standard procedures.Results: Body weight, body mass index (BMI) and waist circumference were found to be significantly (p<0.01) increased when compared with control values. The triglyceride, total homocysteine and fasting plasma glucose (FPG) were markedly high in diabetes as compared to control. The Vitamin B12 and Folic acid levels were significantly (p<0.05) decreased in diabetes as compared to control values. Conclusion: The outcome of this study reveals that high homocysteine level, high triglyceride level and decreased Vitamin B12 and Folic acid levels can be categorized as strong risk factor for early cardiovascular diseases.Key Words: Homocystein, glucose, Type-II diabetes, triglycerides, vitamin B12, cardiovascular disease.